Vodojemy - Brno, Žlutý kopec - Menšíková, Kateřina (Vysoké učení technické v Brně. Fakulta architektury)
Diplomová práce se zabývá oblastí vodojemů na Žlutém kopci, které se nacházejí mezi ulicemi Tomešovou a Tvrdého. Provoz vodojemů byl ukončen v roce 1997 a v současné době hledá TIC Brno námět na jejich využití a zpřístupnění širší veřejnosti. Místo zůstalo z důvodu existence podzemních vodojemů nezastavěné a oblast je pokryta hustou zelení. Díky tomu je charakter místa v kontextu okolní zástavby jedinečný. Návrh tuto skutečnost nejen respektuje, ale snaží se o její podporu. Celá oblast prochází parkovou úpravou a je doplněna o trojici jednopodlažních pavilonů, které svojí různorodou funkcí zajišťují provoz lokality. Původní stavby, které sloužily ke správě podzemních vodojemů jsou zrekonstruovány a jsou začleněny do chodu místa. Důležitou složkou návrhu je také řešení bezbariérového zpřístupnění vodojemů, jejich propojení a instalace optického zařízení Camery Obscury do nejstaršího z vodojemů. Dochází tak k zatraktivnění místa pro návštěvníky.

Master’s thesis focuses on area of historic water reservoirs on Yellow Hill, situated between streets of Tomešova and Tvrdého. They continued to supply Brno with non-potable water until 1997 and TIC is currently looking for a new way to make water reservoirs accesable and more interesting to the general public. Due to the existence of underground reservoirs the site has remained undeveloped and is covered with dense greenery. Thanks to that, the character of the place is in the context of the surrounding build-up area very unique. The proposal not only respects that, but seeks to support it. The whole area is undergoing through new landscape design and is completed by three single-storey pavilions, which with their various functions ensure the operation of the site. The historic buildings that were used to manage the underground reservoirs are renovated and integrated into the operation of the site. An important part of the design is also the solution of barrier-free access to reservoirs, their interconnection and installation of optical device - the Camery Obscury in the oldest of the reservoirs. The whole place becomes more accesible and attractive for visitors.
Reservoirs - Brno, Zluty kopec (Yellow hill)
Keywords: dřevostavba; lepené dřevo; park; pavilon; vodojemy; camera obscura; zeleň; Timber structure; Laminated veneer lumber; park; pavilion; water reservoirs; camera obscura; vegetation